The theme of the double in three writers of the Generation of the 50 - Vega Mendieta, Nehemías (2022)
This article will analyze the theme of the double in three Peruvian narrators of the Generation of 50: Guillermo Bellido Yábar, Rubén Sueldo Guevara, and Felipe Buendía. In this generation, a fantastic aspect developed within the narrative, which was almost ignored by critics until the beginning of this century. One of the recurring topics within this aspect was the theme of the double, which represents the conflict between the concepts of identity and alterity, which can be linked to the social changes that took place in that decade. Guillermo Bellido Yábar, Rubén Sueldo Guevara and Felipe Buendía are little known authors of this generation and had a short narrative production that was published basically in newspapers and magazines, in which the theme of double was treated in a particular way to address the problem of identity. The stories of these authors are characterized by inserting the figure of the doppelgänger in the city, whose presence reveals the fragmentation of the individual in the face of the changes that operate in the city due to modernity. The encounter between the original subject and its double will reflect the crisis of identity experienced by the individual in the urban space.